2008
DOI: 10.1007/s11606-007-0483-y
|View full text |Cite|
|
Sign up to set email alerts
|

Communicating about Alcohol Consumption to Nonharmful Drinkers with Hepatitis C: Patient and Provider Perspectives

Abstract: BACKGROUND:Abstaining from alcohol consumption is generally recommended for patients with Hepatitis C (HCV). However, mixed research findings coupled with a lack of consistent guidelines on alcohol consumption and HCV may influence what healthcare providers tell their HCV patients about drinking. This may be more problematic when advising nonharmful drinkers with HCV, a population for whom consumption would not be a problem in the absence of their HCV diagnosis. OBJECTIVE:This study explores what healthcare pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…This construct therefore reflects an individual’s overall attitude towards the health care system as well as the willingness to interact with health service providers. As prior literature suggests that patients’ adherence is partially determined by aspects of the patient-doctor relationship (Blixen et al, 2008; Vermeire et al, 2001), health management style may be crucial to consider for reducing alcohol consumption.…”
Section: Segmenting Excessive Alcohol Consumersmentioning
confidence: 99%
See 1 more Smart Citation
“…This construct therefore reflects an individual’s overall attitude towards the health care system as well as the willingness to interact with health service providers. As prior literature suggests that patients’ adherence is partially determined by aspects of the patient-doctor relationship (Blixen et al, 2008; Vermeire et al, 2001), health management style may be crucial to consider for reducing alcohol consumption.…”
Section: Segmenting Excessive Alcohol Consumersmentioning
confidence: 99%
“…In particular, no previous study could be found that has utilized psychographic segmentation based on health management styles to segment heavy drinkers for understanding their attitudes and behaviours. This is important as past research demonstrates that aspects of the patient-doctor relationship (Blixen et al, 2008; Vermeire et al, 2001; Sutton et al, 2015) play a key role in reducing alcohol consumption. For example, a recent study demonstrates that aspects of health management styles such as cooperation with doctors, trust in doctors and living a healthy lifestyle are significantly related to alcohol consumption (Perzynski et al, 2011).…”
mentioning
confidence: 99%
“…Hence, recommendations for alcohol abuse counseling for heavy alcohol consumers are empirically-driven, but those for lighter drinkers are not, until more data are obtained. The lack of data and the consequent vagueness of practice guidelines leads to idiosyncratic physician decisions and mixed messages for patients (Blixen et al, 2008). Interventions to reduce excess alcohol consumption are needed.…”
Section: Biopsychosocial Pre-treatment Factorsmentioning
confidence: 99%
“…Despite these measures and guidelines that recommend counseling patients to abstain or moderate alcohol use in the context of HCV, patients may still receive confl icting messages, perhaps in part because of physicians' awareness of evidence gaps (Blixen et al, 2008). Yet even when patients with HCV are counseled appropriately, numerous psychosocial factors may interfere with their ability to comply with recommendations to limit drinking (Perzynski et al, 2011). This study reinforces the need to target HCV-infected patients as a riskier subgroup for alcohol-related risks among HIV-infected populations, and supports research to develop tailored interventions to reduce drinking.…”
Section: Adjusted Mean (U/l)mentioning
confidence: 99%